The Res publica Schefferiana – the correspondence of Johannes Schefferus (1621-1679) - Klein, Andreas (DataverseNO, 2020)
This dataset lists preliminary results of research on the correspondence of philologist Johannes Schefferus (1621-1679). It was created to accompany my doctoral dissertation «Early Modern Knowledge about the Sámi: A History of Johannes Schefferus’ Lapponia (1673) and its Adaptations» dealing with the first-ever monograph on the Sámi people of the Fennoscandian peninsula, and its adaptations published in the seventeenth and eighteenth centuries. In the dissertation, I analyse the role correspondence played in the coming into existence and further development of the Lapponia project. The dataset is an extension of the register of Schefferus’ correspondence found in Eric Michael Fant’s (1754-1817) biography of Schefferus "Minne öfver Joh. Schefferus", published in Stockholm in 1782. It lists all letters found in six volumes (UUB G 260 and G 260 a-e) at the manuscript collection of Uppsala University Library, further letters scattered in other volumes and some copies. Parts of Schefferus’ correspondence has been published in print or listed elsewhere. This is noted in all known cases. The .pdf- and .xlsx-versions contain hyperlinks to the respective digitized versions or archival entries.